Family Rhabderemiidae Topsent, 1928. Pp. 511–514. In: Hooper, J.N.A.; Van Soest, R.W.M. (2002 [2004]) - Hooper, J. N. A. (Systema Porifera. A Guide to the Classification of Sponges, 2002)
Rhabderemiidae Topsent (Demospongiae, Poecilosclerida) contains four nominal genera of which only one is now valid, currently with 26 described species predominantly from shallow waters of all tropical and warm temperate seas (with one deep water species known from 1360 m depth). The family is still of uncertain relationship, having a unique apomorphy in the form of smooth or spined rhabdostyles bearing a basal spiral twist, and peculiar usually rugose microscleres resembling oxeas or toxas (thraustoxeas), sigmas (spirosigmata, thraustosigmata) and microstyles, although these are probably analogous to toxas and sigmas found in other poecilosclerids. Species are usually thinly encrusting but also include branching, club-shaped, digitate or massive forms, usually fleshy, with species differing mainly in their microsclere composition and geometry and spicule dimensions.